Parents' years in Sweden and children's educational performance - Christopher D. Smith; Jonas Helgertz; Kirk Scott (IZA Journal of Migration, 2016)
This paper assesses the intergenerational effect of immigrant parents' incorporation experiences, measured as time in Sweden, on the educational performance of their children, using full Swedish population registry data for 22 cohorts. Employing family fixed-effects, we examine final course grades and national standardized test scores in Swedish and math by parents'country of origin. Results show a positive effect of parents' time in Sweden on their children's performance in Swedish, but not for math performance. These results demonstrate the importance of parents' linguistic acculturation on their children' educational performance.
Keywords: I21; J15; J62; 330; Intergenerational mobility; Immigrant incorporation; Years since migration; Second generation; Family fixed-effects